Water Contact Angle: Time Dependence and Lubricant Dynamics on Hard Disk Media - Akinobu Wakabayashi (Japanese Society of Tribologists, 2008)
The water contact angles of disks coated with Z-tetraol and A20H decreased gradually with time, starting from the initial value of approximately 105° and approaching a value below 100° in 20 seconds. The cause of temporal change was the interaction between the polar end groups of lubricant molecules and water molecules of the droplet. In the measurement environment, a part of the polar end groups was attracted to a polar droplet from the carbon surface. The contact angle consequently decreased. However, on the robust lubricant films prepared by using the ester lubricants with long-UV (254 nm) irradiation, the temporal changes were not observed. It attests to the formation of chemical bonds without polar end groups. It is proposed that the temporal change of the contact angles reflected dynamic behavior of the lubricant molecules on the disk surface.